Correlates of prediabetes and type II diabetes in US South Asians: findings from the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study - Shah, Arti D.; Vittinghoff, Eric; Kandula, Namratha R.; Srivastava, Shweta; Kanaya, Alka M. (Annals of epidemiology, 2015)
In this study, we aim to elucidate the role of sociodemographic, lifestyle, and cultural factors in prediabetes and diabetes in South Asian immigrants to the United States, a population at high risk of type II diabetes. We performed a cross-sectional analysis of a community-based cohort of 899 South Asians without known cardiovascular disease from the Mediators of Atherosclerosis in South Asians Living in America study. Glycemic status was determined by fasting glucose, 2-hour postchallenge glucose, and use of diabetes medication. We used multinomial logistic regression models to estimate the independent associations of sociodemographic, lifestyle, and cultural factors with prediabetes and diabetes, adjusting for confounders identified using directed acyclic graphs. Approximately 33% of participants had prediabetes and 25% had diabetes. In multivariate analyses, an independent correlate of prediabetes was low exercise. Additional covariates associated with diabetes included lower family income, less education, high chronic psychological burden score, and greater time spent watching television; and fasting monthly or annually was inversely associated with diabetes prevalence. We found several modifiable risk factors associated with prediabetes and diabetes that may help guide diabetes prevention interventions for South Asian immigrants to the United States. •Cross-sectional analysis of large cohort of US South Asians without cardiac disease•There was a high prevalence of prediabetes (33%) and diabetes (25%)•Significant difference in diabetes prevalence between the two study sites•Lower income, less education, and more time watching television associated with diabetes•More exercise; fasting monthly/annually associated with lower diabetes prevalence